Analysis of Length-Weight Relationship of Mackerel Scad Scad (Decapterus sp.) Landed in Ampenan Fish Market, West Nusa Tenggara Province - Dwiyanti, Septiana; Muahiddah, Nuri (Aquaculture Department, University of Mataram, 2024)
The catch of fishermen around Ampenan waters is dominated by Mackerel scad and rucah. Fish caught by fishermen around Ampenan waters are usually landed at the Ampenan fish market to be traded. Mackerel scad (Decapterus sp.) is a pelagic fish that lives in groups and is spread out. Mackerel scad (Decapterus sp.) In addition to having a cheap price, Mackerel scad (Decapterus sp.) also has good nutritional value so that Mackerel scad is included in important economic products. The biological aspect in the form of the relationship between length and weight in Ampenan waters is important to study in efforts to manage fisheries in West Nusa Tenggara, especially Ampenan. Efforts to manage fisheries through fisheries biology information related to the relationship between length and weight aim to determine the variation in weight and length of Mackerel scad (Decapterus sp.) individually or in groups as an indicator of the productivity, health and growth conditions of Mackerel scad obtained in these waters. The study was conducted in March 2024 using survey methods and regression analysis. The number of samples used in this study was 50 Mackerel scad (Decapterus sp.) which were taken randomly at the Ampenan fish market. The results of linear regression and graphs of the relationship between the length and weight of Mackerel scad samples (Decapterus sp.) in this study produced a regression equation Y = 0.04855x 2.2973 with a coefficient of determination (r2) of 62% and a b value of 2.29, meaning b <3 which means negative allometric which means that length growth is faster than weight growth.